Aging, Cultivation, and Transcendence in Confucianism - Seongmin Hong (Society for Spirituality Studies, 2021)
This study aims to investigate the spiritual model to be pursued in old age, focusing on the spiritual cultivation and the moral transcendence in Confucianism. For this purpose, it adopts a comparative methodology to compare the theory of gerotranscendence with Neo-Confucian texts in three steps. First, it investigates how the gerotranscendence theory can be interconnected with Confucianism, which entails distinctive spiritual characteristics. Second, it examines how Confucianists immerse themselves in self-cultivation and gain emancipated innocence. Here it clarifies two ways of cultivation: keeping reverence in tranquility to return to one’s essential state and embodying the truth to transform into a cosmic Self. And finally, it considers the metaphysics of life and the cosmic unity in Confucianism, and a decent death in the state of moral transcendence. In sum, the study claims that old age is to be understood as a significant period of gaining infinite growth and achieving the completion of spirituality, not just as a period of senescence, and Confucian spiritual cultivation may have a beneficial effect on the lives of seniors today.